2013
DOI: 10.1128/aem.01406-13
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of creB in Aspergillus oryzae Increases Secreted Hydrolytic Enzyme Activity

Abstract: dAspergillus oryzae has been used in the food and beverage industry for centuries, and industrial strains have been produced by multiple rounds of selection. Targeted gene deletion technology is particularly useful for strain improvement in such strains, particularly when they do not have a well-characterized meiotic cycle. Phenotypes of an Aspergillus nidulans strain null for the CreB deubiquitinating enzyme include effects on growth and repression, including increased activity levels of various enzymes. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Co-immunoprecipitation experiments have shown that CreB and CreC proteins function together as a complex during repression or derepression condition. It was proved that CreB-CreC deubiquitination complex has its role in CCR as deletion of Cre2 and CreB in T. reesei and A. oryzae respectively enhanced the secretion levels of hydrolytic enzymes [ 13 , 144 ]. The CreB-CreC deubiquitination complex eradicates ubiquitin moieties from CreA and other substrates thereby modifying the protein [ 79 ].…”
Section: Key Regulators Of Ccr In Filamentous Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Co-immunoprecipitation experiments have shown that CreB and CreC proteins function together as a complex during repression or derepression condition. It was proved that CreB-CreC deubiquitination complex has its role in CCR as deletion of Cre2 and CreB in T. reesei and A. oryzae respectively enhanced the secretion levels of hydrolytic enzymes [ 13 , 144 ]. The CreB-CreC deubiquitination complex eradicates ubiquitin moieties from CreA and other substrates thereby modifying the protein [ 79 ].…”
Section: Key Regulators Of Ccr In Filamentous Fungimentioning
confidence: 99%
“…Mutants of CCR in A. nidulans have been mapped to define the genes CreA (Cre = catabolite responsive elements), CreB , CreC and CreD [ 8 , 9 , 10 , 11 ]. In addition, other species of Aspergillus such as A. oryzae and A. flavus have also been adequately studied in relation to CCR [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of A. oryzae creB resulted in relief from CCR and increased production of ␣-amylase (23,24). We generated the creB and creD double-disruption mutant strain to investigate the involvement of creD in carbon catabolite derepression in the creB disruption mutant (see Fig.…”
Section: Figmentioning
confidence: 99%
“…The CreB-CreC DUB complex has been proposed to be involved in CCR because mutations in CreB and CreC alleviate CCR (Hynes and Kelly 1977). Deletion of creB and cre2 in A. oryzae and T. reesei, respectively, resulted in elevated levels of secreted hydrolytic enzymes (Denton and Kelly 2011;Hunter et al 2013). Furthermore, recent studies have indicated that FbxA, a protein involved in ubiquitination of target proteins, is involved in creA messenger RNA (mRNA) accumulation (Colabardini et al 2012).…”
mentioning
confidence: 99%